Therapeutic efficacy and safety of various botulinum toxin A doses and concentrations in spastic foot after stroke: a randomized controlled trial - Jiang Li; Ru Zhang; Bo-li Cui; Yong-xiang Zhang; Guang-tao Bai; Si-shan Gao; Wen-jian Li (Neural Regeneration Research, 2017)
No recommended guidelines currently exist for the therapeutic concentration or dose of botulinum toxin type A (BTXA) injected into the muscle to treat limb spasticity. Therefore, in this randomized controlled trial, we explored the safety and efficacy of two concentrations and two doses of BTXA in the treatment of spastic foot after stroke to optimize this treatment in these patients. Eligible patients (n = 104) were randomized into four groups. The triceps surae and tibialis posterior on the affected side were injected with BTXA at one of two doses (200 U or 400 U) and two concentrations (50 U/mL or 100 U/mL). The following assessments were conducted before as well as 4 days and 1, 2, 4, and 12 weeks after treatment: spasticity, assessed using the modified Ashworth scale; basic functional mobility, assessed using a timed up and go test; pace, assessed using a 10-meter timed walking test; and the ability to walk, assessed using Holden's graded scale and a visual analog scale. The reported results are based on the 89 patients that completed the study. We found significant differences for the two doses and concentrations of BTXA to improve the ability of patients to walk independently, with the high-dose/low-concentration combination providing the best effect. Onset and duration of the ameliorating effects of BTXA were 4–7 days and 12 weeks, respectively. Thus, BTXA effectively treated foot spasms after stroke at an optimal dose of 400 U and concentration of 50 U/mL.